ANALYZING THE FACTORS INFLUENCING THE SUCCESS RATES OF DENTAL IMPLANTS, INCLUDING PATIENT DEMOGRAPHICS, SURGICAL TECHNIQUES AND IMPLANTS DESIGN (The Research of Medical Science Review, 2024)
Dental implants have become a cornerstone in restorative dentistry, with success rates influenced by various factors, including patient demographics, surgical techniques, and implant design. Understanding these factors is crucial for optimizing treatment outcomes, This study aimed to analyze the factors influencing the success rates of dental implants, focusing on patient demographics, surgical methods, and implant design, A retrospective cohort design was used to assess data from 774 patients (445 males, 252 females) who underwent 1,988 dental implant procedures between 2015 and 2024. Demographic factors, surgical techniques (submerged, non-submerged, flapless, and bone grafting), and implant design (standard vs. short length, rough vs. polished surfaces) were evaluated. Statistical analysis was performed using SPSS and Stata, including chi-square tests, logistic regression, and Kaplan-Meier survival analysis, Age and smoking history were significant predictors of implant success, with older patients and smokers exhibiting lower success rates. Surgical techniques such as submerged implants and flapless procedures showed higher success rates, while bone grafting was associated with increased failure. Implant design also influenced outcomes, with standard-length and rough-surfaced implants showing superior success compared to short-length and polished variants, Patient age, smoking, and implant-related factors like surgical technique and design significantly impact implant success rates. Personalized treatment strategies, considering these factors, are essential for improving dental implant outcomes.